다래나무의 tert-butyl Hydroperoxide로 유도된 산화적 스트레스에 대한 간 보호 효과 - 조은혜; 강경수; 이희주; 김철영; 신일식; 노주원 (대한암예방학회, 2011)
The fruits and leaves of Actinidia arguta are a well-known Korean folk medicine for treatment of jaundice, fever, acute hepatitis and bleeding by an external wound. The purpose of this study was to investigate the hepatoprotective effect of A. arguta on tert-butyl hydroperoxide (t-BHP) induced oxidative stress in HepG2 human liver cancer cells. Cell viability, generation of reactive oxygen species, quantification of total glutathione, total polyphenolic compounds were evaluated in this study. Pretreatment of the extract from A. arguta extract, butanol and ethyl acetate fractions strongly prevented cytotoxicity induced by t-BHP. Reactive oxygen species generation induced by t-BHP was significantly decreased when the cells were pretreated for 24 h with either 10∼40μg/ml extract or hexane, ethyl acetate, butanol fractions. In addition, lower levels of total glutathione (GSH) caused by t-BHP in HepG2 cells were recovered by a pre-treatment with extract and 3 fractions. The contents of total polyphenolic compounds were also determined using a modified Folin-Ciocalteu colorimetric method. The ethyl acetate and butanol fractions had high phenolic compounds, and they showed 136.61μg/100 g and 211.64μg/100 g, respectively, suggesting that these antioxidants content was correlated with their hepatoprotective activity. Therefore, these result suggest that the A. arguta could be a potential candidate of hepatoprotective agents against oxidative stress. (Cancer Prev Res 16, 74-79, 2011)